Meningkatkan Kepercayaan Diri Anak-Anak Panti Asuhan Ahbaabul Mukhtar Semarang melalui Pelatihan Public Speaking - Rizki Nur Rochim; Abdullah Yazid Taqiyyudin Al Fathu; Ahmad Rifa’i Ma’ruf; Muhammad Farhan Surya Purnama; Fikri Fadhlu Rahman; Zaky Hilmy; Muhammad Arfa Praditiya; Muhammad Khoir Luqman; Muhammad Aulia Akbar; Anindita Evelyn Jessica Putri (Pakis Journal Institute, 2026)
This community service program was conducted in response to the low level of self-confidence among orphanage children, particularly in their public speaking abilities. Preliminary observations at the Ahbaabul Mukhtar Orphanage in Semarang indicated that many participants experienced anxiety, lacked confidence to perform, and had limited ability to express ideas in a structured and communicative manner. Therefore, this program aimed to enhance self-confidence through a structured and participatory public speaking training. The implementation consisted od several stages, including observation, orientation, material delivery, practice sessions and evaluation. The training materials covered fundamental aspects of public speaking, such as vocal control, articulation, intonation, body language and anxiety management techniques. The learning process was supported by ice-breaking activities and direct practice to increase participant engagement. The result indicated that a significant improvement in participants’ self-confidence, as reflected in their increased willingness to perform in public, improved ability to respond to questions systematically, and more effective use of nonvrebal communication. Additionally, the program contributed to strengthening social interaction and fostering a positive environtment within the orphanage. However, time limitations affected the depth of material delivery. Therefore, follow-up programs are necessary to ensure the sustainability of the outcomes. Overall, the public speaking training proved to be an effective approach to improving self-confidence among orphanage children.